ASSESSING THE WILLINGNESS TO PAY FOR CONSERVATION AND MANAGEMENT OF WETLANDS AT JAGDISPUR RESERVOIR IN KAPILVASTU DISTRICT OF NEPAL - Gyawali, Rama; Sharma, Gyan Bandhu; Shrestha, Jiban (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
Wetlands are one of the world's most productive ecosystems. They have significant ecological, economic, cultural, and recreational significance. However, wetlands are being misused and degraded; therefore, wise and sustainable use of wetlands, conservation and management of wetlands resources are critical at the local level. Community-based conservation is a method of managing wetlands near settlements sustainably. The objective of this study was to determine local people's willingness to pay (WTP) for community-based conservation and management activities, as well as the factors which influence it, at the Jagdispur Reservoir in Nepal's Kapilvastu district. A total of 62 households were surveyed. Household surveys and key informant interviews were conducted. Contingent valuation was used to elicit WTP, while regression analysis identified significant determinants. Thirteen provisioning, regulating, cultural and supporting services were identified, including irrigation, fisheries, tourism and biodiversity. Of 62 households, 67% expressed WTP averaging NRs 3,351 (US 25.38) annually. WTP was higher for proximal households, reflecting greater dependence. Cash payments dominated, but labor contributions were also substantial. Age, income, participation in conservation, and distance from wetlands positively and significantly influenced WTP. Whereas education, gender, ethnicity and number of family members did not. The findings indicate a high value placed on sustaining wetland services, justifying investment in conservation and wise use. Follow-up research on governance, benefit sharing and sustainable financing is recommended to translate WTP into effective action. Overall, the results provide important baseline data to guide policies and collective action for wetland stewardship.